2017
DOI: 10.1177/1833358317697470
|View full text |Cite
|
Sign up to set email alerts
|

Best practice in the management of clinical coding services: Insights from a project in the Republic of Ireland, Part 2

Abstract: Examples of best practice were found in the study hospitals but there were also areas for improvement. Coding managers would benefit from greater support in the form of increased opportunities for management training and a better method for calculating CC workforce numbers. A career pathway is needed for CCs to progress from entry to expert CC, mentor, manager and quality controller. Most hospitals could benefit from investment in infrastructure that places CCs in a physical environment that tells them they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The majority (75%) of CCs were employed at Grade level 4 (Healthcare Pricing Office, 2015). A fuller discussion of grade levels is contained in Part 2 (Reid et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority (75%) of CCs were employed at Grade level 4 (Healthcare Pricing Office, 2015). A fuller discussion of grade levels is contained in Part 2 (Reid et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Part 2 (Reid et al, 2017) will discuss the coding manager background, preparation and style, CC workforce adequacy, pay grades and a career pathway for CCs, and the physical and psychological work environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the authors' work in data quality assessment and improvement conducted in Australia [4], Ireland [5], [6], Singapore [7], Kingdom of Saudi Arabia [8], and Fiji, a set of common factors were identified that undermine data quality improvement initiatives including poor workforce development, fragmented workforce deployment, ambiguous role definition, poor workforce motivation and deficient strategic direction.…”
Section: Introductionmentioning
confidence: 99%
“…Rowlands et al (2016) explained that the clinicians who are responsible for the documentation in the medical record that underpins the coded data are not necessarily educated about how to document effectively for good patient care and the production of good data for multiple downstream uses. Reid et al (2017a, 2017b) in their two part article about Best Practice in the Management of Clinical Coding Services: Insights from a Project in the Republic of Ireland also described issues with poor documentation, lack of clinician involvement with data quality and the need to support the clinical coding workforce in a way that makes them feel valued. A series of articles published by Dimitropoulos et al (2019a, 2019b, 2019c) in the Health Information Management Association of Australia’s (HIMAA) profession practice journal, HIM-Interchange , reported on findings from a clinical coding workforce survey conducted by the National Centre for Classification in Health (NCCH) and a workshop conducted by the NCCH at the 35th HIMAA and NCCH National Conference.…”
mentioning
confidence: 99%